Stability of Lifestyle Behavior – The Answer to Successful Cognitive Aging? A Comparison of Nuns, Monks, Master Athletes and Non-active Older Adults - Schott, Nadja; Krull, Katja (Frontiers in Psychology, 2019)
Background. Epidemiological studies of the effect of physical activity on cognition demon-strated an inverse relationship between physical activity and cognitive decline. However, such health behaviors are hardly invariable over time. The relative homogeneity of the adult lifestyle of nuns / monks as well as master athletes reduces the likelihood of confounding due to differences in their participation in regular life-long physical activities. The purpose of this study was to determine if there were differences in cognitive functions between nuns/monks, master athletes and sedentary, but otherwise healthy older adults. Additionally, we examined associations between demographic variables (education, sex, age), BMI, physi-cal activity, exercise, and fitness and cognitive performance. Methods. We recruited three groups of healthy participants without cognitive deficits: (1) Nuns / Monks (NM; n=20; age 77.5 ± 5.56; 5 M, 15 W), (2) Master Athletes (MA; n=20; age 76.5 ± 5.33; 12 M, 8 W), and (3) Sedentary (S; n=20; 76.4 ± 5.96, 6 M, 14 W). Cognitive per-formance (working memory, inhibition) was measured with a n-back task and a flanker task, participation in physical activities with the „German-PAQ-50+“, and physical fitness with the 30s chair stand and arm curl test. Results. As predicted, ANOVA comparing groups revealed the three groups differed in cogni-tion, physical activity, and physical fitness with inactive older adults performing lower on all tests than the other two groups. Hierarchical regression analyses revealed a positive influ-ence of lifestyle stability on accuracy and reaction time for working memory and inhibitory performance. Nuns/monks revealed the highest correlations between fitness and cognitive performance. Conclusion. Life-long stability of an active lifestyle may confer benefits to some aspects of working memory, attention and inhibitory control. Longitudinal studies are recommended to further examine the causal relationship of lifestyle stability and cognitive function in such specific cohorts.